A rare human centenarian variant of SIRT6 enhances genome stability and interaction with Lamin A. (1st February 2023) - Simon, Matthew; Yang, Jiping; Gigas, Jonathan; Earley, Eric J; Hillpot, Eric; Zhang, Lei; Zagorulya, Maria; Tombline, Greg; Gilbert, Michael; Yuen, Samantha L; Pope, Alexis; Van Meter, Michael; et al.
Abstract :